Cathodic stripping voltammetric procedure for determination of some inorganic arsenic species in water, soil and ores samples - Junsomboon J. (2014)
Square wave cathodic stripping voltammetry was developed for determination of As(III) and/or As(V) in water, soil, and ore samples. The method was based on electrodeposition of As(III) on a hanging mercury drop electrode (HMDE) as a copper-arsenic intermetallic compound, which was further reduced to arsine at a higher negative potential in the stripping step. Deposition was performed in an electrolyte solution of 1 M HCl with 10 mg L-1 Cu(II), by applying a constant potential of -0.40 V vs Ag/AgCl to the HMDE for 60 s at a stirring rate of 2,000 rpm. Stripping step was carried out by applying a square wave waveform in the potential range from -0.40 to -1.00 V. A voltammogram was obtained with peak potential at -0.78 V giving peak current linearly proportional to As(III) concentration up to 50 μg L-1. The concentration of Cu(II) and deposition time were interrelated affecting the sensitivity of arsenic determination. With a fixed deposition time of 60 s, a narrow concentration range of Cu(II), 5-10 mg L-1 gave the highest sensitivity. Standard addition method was applied for quantification in order to account for effect of sample matrix. The detection limit of the method was 0.3 μg L-1 As(III) and the relative standard deviation for 5 μg L-1 As(III) (n =11) was 3.6%. As(V) concentration was determined after reduction to As(III) by using 80 mg L-1 of thiosulfate. The developed method was applied to the analysis of water, soil, ores leachate and ores digest samples. The results were in good agreement with those obtained by HG-AAS method and the certified value of soil certified reference material. Recoveries in range of 83-108% were obtained for water samples. The proposed method is simple, convenient, and low reagent consumption.